Becoming Gender Relevant: A Pre/Post Examination of University Students’ Attitudes and Perceptions of Gender Constructs in Education and Society - Sherrie Carinci (Adult Education Research Conference, 2010)
Colleges and universities have many lofty goals and objectives. One such mission is to enlighten our country’s future leaders on social, economic, and political complexities of our diverse society, while engaging our students to be innovative thinkers and agents of social change (Atwell, 1993; Carinci & Wong, 2009; Pierce, 2003). In order to help students gain an understanding of issues of race, class, and gender, university courses have been created to help with the dialogue on social justice and inclusion of all in our society. Though there is minimal research on the subject, it is this scholar’s opinion that students who graduate from colleges and universities are unaware of the discriminating practices which exist in America’s schools. If discussed at all, most college students receive brief explanations as to the gender issues facing students in school today. Such topics as teacher’s interaction patterns with students, lack of females represented in school curriculum, and issues of harassment and bullying are missing from the dialogue and education preparing students to become future educators and leaders in our society (Sadker, 2003). As part of university education, students need to recognize that the discussion of gender, both female and male, needs to be paramount when educating our future leaders, teachers, and business community.